Giving Lemna Minor and Mud to the Growth of Tubifex sp. - Mahendra, Mahendra; Damara, Doni; Nufus, Mursidatun; Putri, Vira Riana (Budapest International Research in Exact Sciences (BirEx) Journal, 2019)
This study aims to determine the effect of the use of a combination of lemna minor substrates and mud on the biomass of the population of Tubifex sp. This research is experimental, with a completely randomized design (CRD), with five levels of treatment P1 = 100% (lemna minor ) + 2,000 gr (mud), P2 = 75% (lemna minor ) + 2,000 gr (mud), P3 = 50 % (lemna minor ) + 2,000 gr (mud), P4 = 25% (lemna minor) + 2,000 gr (mud), P5 = 0% (lemna minor) + 2,000 gr (mud). Data obtained from research results in analysis of variance (ANOVA) and in further testing with the Smallest Significant Difference test. The main parameters observed were the number of population and biomass of Tubifex sp. The results of the study showed that the combination of Lemna minor substrate and mud significantly (p <0.05) on the growth of biomass and the population of Tubifex sp. The best results were found in the treatment with the treatment formulation P1 = 100% (lemna minor ) + 2,000 gr (mud) which produced a population of 6,250 ind / gr and biomass 8.60 gr / m2.